1996
DOI: 10.1080/09593331708616426
|View full text |Cite
|
Sign up to set email alerts
|

Column Studies of Copper(II) and Nickel(II) Ions Sorption on Palm Pressed Fibres

Abstract: The efficiency of palm pressed fibres (PPF) in removing copper(II) and nickel(II) ions from solution was investigated in column experiments. Homogeneous column studies show that metal sorption increased with lower flow rate, higher bed-depth and lower metal ion concentration. Bed-depth service time (BDST) studies show that the results agree with the BDST model proposed by Hutchins [1]. The mixed media studies using sand-soil PPF combination demonstrated that PPF can be an efficient sorbent in the prevention of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It was found that by reducing the flow rate, the service time increased and hence the volume of adsorbate solutions treated was effectively increased. This flow rate dependence can be explained by the kinetics controlling process [27]. The lower the flow rate, the longer the contact time and hence the greater the interaction between adsorbate and adsorbent.…”
Section: Column Operationsmentioning
confidence: 98%
“…It was found that by reducing the flow rate, the service time increased and hence the volume of adsorbate solutions treated was effectively increased. This flow rate dependence can be explained by the kinetics controlling process [27]. The lower the flow rate, the longer the contact time and hence the greater the interaction between adsorbate and adsorbent.…”
Section: Column Operationsmentioning
confidence: 98%